2020
DOI: 10.1111/febs.15203
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a bacterial copper‐dependent lytic polysaccharide monooxygenase with an unusual second coordination sphere

Abstract: Lytic polysaccharide monooxygenases (LPMOs) are copper-dependent enzymes involved in the degradation of recalcitrant polysaccharides such as cellulose or chitin. LPMOs act in synergy with glycoside hydrolases such as cellulases and chitinases by oxidatively cleaving a number of glycosidic bonds at the surface of their crystalline substrate(s). Besides their role in biomass degradation, some bacterial LPMOs have been found to be virulence factors in some human and insect pathogens. Photorhabdus luminescens is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 77 publications
4
25
0
Order By: Relevance
“… Structure of the Pl AA10 LPMO enzyme (PDB code: 6T5Z) 15 and of its active site, with special focus on the copper center and its first coordination sphere. Bond distances shown in Å.…”
Section: Introductionmentioning
confidence: 99%
“… Structure of the Pl AA10 LPMO enzyme (PDB code: 6T5Z) 15 and of its active site, with special focus on the copper center and its first coordination sphere. Bond distances shown in Å.…”
Section: Introductionmentioning
confidence: 99%
“…LPMOs act synergistically with glycoside hydrolases such as cellulases and chitinases by oxidatively cleaving several glycosidic bonds at the surface of their crystalline substrate(s). In addition to their role in biomass degradation, some bacterial LPMOs act as virulence factors in several human and insect pathogens ( 34 ). AT730_22220 is carotenoid 1,2-hydratase (CrtC), which catalyzes the selective addition of water to an isolated carbon-carbon double bond ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Literature analysis of the occurrence of lytic polysaccharide monooxygenases (LPMOs) found in various pathosystems. (a, b) Number of research articles reporting an LPMO (or LPMO‐like) shown to be relevant by either transcriptomic, proteomic and/or enzyme characterisation in different emitters (Kawada et al ., 2008; Chaudhuri et al ., 2010; Valente et al ., 2011; Stauder et al ., 2012; Wong et al ., 2012; Yakovlev et al ., 2012; Garcia‐Gonzalez et al ., 2014; Loose et al ., 2014; Chiu et al ., 2015; Hamre et al ., 2015; Huang et al ., 2015; Paspaliari et al ., 2015; Zhang et al ., 2015; Mekasha et al ., 2016; Shukla et al ., 2016; Liu et al ., 2017, 2018, 2020; Hegnar et al ., 2019; Yadav et al ., 2019; Garcia‐Santamarina et al ., 2020; Labourel et al ., 2020; Li et al ., 2020; Munzone et al ., 2020; Askarian et al ., 2021; Polonio et al ., 2021; Sabbadin et al ., 2021a,b; Yue et al ., 2021), and displayed as (a) a function of the year of publication per emitter and (b) an emitter–target map, in which the circle size indicates the number of articles and the colour indicates the protein family. Note that the ‘preferred target’ shows the potential target of the emitter, and not necessarily the target of the LPMO, which in several cases remains to be fully demonstrated (see main text).…”
Section: Emerging Biological Functionsmentioning
confidence: 99%